Effects of prior concentric training on eccentric exercise induced muscle damage. Issue 2 (1st April 2003) - Gleeson, N; Eston, R; Marginson, V; McHugh, M
Abstract : Background: Exercise induced muscle damage (EIMD) from strenuous unaccustomed eccentric exercise is well documented. So too is the observation that a prior bout of eccentric exercise reduces the severity of symptoms of EIMD. This has been attributed to an increase in sarcomeres in series. Recent studies have suggested that prior concentric training increases the susceptibility of muscle to EIMD following eccentric exercise. This has been attributed to a reduction of sarcomeres in series, which decreases muscle compliance and changes the length-tension relation of muscle contraction. Objective: To assess the effects of prior concentric training on the severity of EIMD. Methods: Four men and four women (mean (SD) age 21.1 (0.8) years) followed a four week concentric training programme. The elbow flexor musculature of the non-dominant arm was trained at 60% of one repetition maximum dynamic concentric strength performance, three times a week, increasing to 70% by week 3. After three days of rest, participants performed 50 maximal isokinetic eccentric contractions on both arms. All participants gave written informed consent before taking part in this study, which was approved by the school ethics committee. Strength, relaxed arm angle (RAA), arm circumference, and soreness on active extension and flexion were recorded immediately before eccentric exercise, one hour after, and at 24 hour intervals for three days. Data were analysed with fully repeated measures analyses of variance. Results: Strength retention was significantly (p<0.01) greater in the control arm than the trained arm (84.0 (13.7)%, 90.4 (14.7)%, 95.2 (10.5)%, 103.5 (7.6)% v 75.5 (11.3)%, 77.6 (15.3)%, 80.1 (13.9)%, 80.9 (12.5)%) at one, 24, 48, and 72 hours respectively. Similarly, soreness was greater in the trained arm (0.7 (0.6), 3.1 (1.4), 3.0 (1.5), 1.9 (2.3)) than in the untrained arm (0 (0.2), 1.6 (1.3), 1.4 (0.6), 0.6 (0.4)) at one, 24, 48, and 72 hours respectively (p<0.05). Concentric training induced a significant reduction in RAA (165.2 (6.7)° v 157.3 (4.9)°) before the eccentric exercise bout (p<0.01). This was further reduced and remained lower in the trained arm at all time points after the eccentric exercise (p<0.01). The arm circumference of the concentrically trained arm was significantly greater than baseline (p<0.05) at 72 hours (30.3 (2.9) v 29.8 (3.3) cm). Conclusions: These findings extend the understanding of the effects of prior concentric training in increasing the severity of EIMD to an upper limb exercise model. The inclusion of concentric conditioning in rehabilitation programmes tends to exacerbate the severity of EIMD in subsequent unaccustomed exercise. However, where concentric conditioning is indicated clinically, the net effect of conditioning outcome and EIMD may still confer enhanced strength performance and capability to dynamically stabilise a joint system.